The identification of internal and external attractiveness factors for water parks as tourist destination products - Cieślikowski, Krzysztof; Brusokas, Andrius (Turyzm/Tourism, 2022)
The aim of the article is to indicate the key issues in water park management, taking into account internal and external conditions of their attractiveness as tourist destination products using the example of Śląskie (Silesian) Voivodeship. In order to achieve this, market analysis of water parks in Poland was undertaken, as well as analyses and syntheses from a questionnaire (especially with regard to theoretical aspects), reports and other studies on themed parks in the strict sense of water parks both worldwide and in Poland, with particular emphasis on Śląskie Voivodeship. The research described in the article indicates a wide spectrum of factors for water park attractiveness as tourist products of settlements and regions. The authors, after market analysis and customer opinions expressed on internet portals devoted to water parks (including ParkiWodne.pl and posted on Google.com), divide these factors into internal (depending on the administration of the facility) and external (on which the administration of the facility has no influence) which are essential for the attractiveness of water parks. Research and inference focus on identifying the attractiveness factors for water parks not only as places for active leisure for both residents and visitors, but as places that are particularly capital-intensive during construction and maintenance. The analyzed conditions for the functioning and development of water parks can be used by their managers and as a regional tourist product to prepare and carry out marketing research taking into account the specificity of their operation.